1999
DOI: 10.1038/sj.cdd.4400465
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction of apoptosis by capsaicin in transformed cells: the role of reactive oxygen species and calcium

Abstract: Capsaicin is a vanilloid quinone analog that inhibits the plasma membrane electron transport (PMOR) system and induces apoptosis in transformed cells. Using a cytofluorimetric approach we have determined that capsaicin induces a rapid increase of reactive oxygen species (ROS) followed by a subsequent disruption of the transmembrane mitochondrial potential (DC m ) and DNA nuclear loss in transformed cell lines and in mitogen activated human T cells. This apoptotic pathway is biochemically different from the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 45 publications
(45 reference statements)
8
114
0
Order By: Relevance
“…Upstream activation of the arachidonate cascade leads to redox unbalance and organelle disruption, which both favor cytochrome c release, then caspases act as downstream executioners of the death program. In this context, it seems noteworthy that also capsaicin-induced PCD occurs through intracellular calcium rise, imbalance of the redox level, and drop in mitochondrial membrane potential (43), further strengthening the hypothesis that AEA is acting through vanilloid receptors. Scheme I summarizes the series of events responsible for AEA-induced cell death.…”
Section: Aea-induced Pcd Is Mediated By Vanilloidmentioning
confidence: 87%
“…Upstream activation of the arachidonate cascade leads to redox unbalance and organelle disruption, which both favor cytochrome c release, then caspases act as downstream executioners of the death program. In this context, it seems noteworthy that also capsaicin-induced PCD occurs through intracellular calcium rise, imbalance of the redox level, and drop in mitochondrial membrane potential (43), further strengthening the hypothesis that AEA is acting through vanilloid receptors. Scheme I summarizes the series of events responsible for AEA-induced cell death.…”
Section: Aea-induced Pcd Is Mediated By Vanilloidmentioning
confidence: 87%
“…To test our assumption, we sought to determine whether buffering the level of [Ca 2ϩ ] c with a cell permeant Ca 2ϩ chelator could inhibit CDDO-induced apoptosis. We pretreated COLO 16 cells with BAPTA acetoxymethyl ester, a cell-permeant agent that is hydrolyzed in the cytoplasm to yield the Ca 2ϩ chelator BAPTA (29), to determine whether we could buffer the increase in [Ca 2ϩ ] c caused by CDDO treatment. As illustrated in Fig.…”
Section: Cddo Promotes Distinct Cellular and Subcellular Alterations mentioning
confidence: 99%
“…41,42 For instance, it has been shown that the disruption of calcium homeostasis can trigger apoptosis, 56 that some apoptotic pathways lead to an increase in the concentration of intracellular calcium, 57 and that calcium chelators inhibit cell death in some systems, 58 but not all. 34,59,60 We observed that MGs induce a sustained elevation of intracellular calcium which implicates both a flux from extracellular source as well as mobilization of intracellular stores (Figure 2). Of interest are the distinct kinetics and intensity in intracellular calcium rises seen with the different MGs.…”
Section: Discussionmentioning
confidence: 96%
“…61 Nevertheless, while derivatives of MGs induce a calcium flux, they do not appear, under the conditions tested, to be essential for cell death induction, as also shown with other apoptotic experimental systems. 34,59,60,62 The exact mechanism by which MGs induce apoptosis is currently unknown. It is conceivable that MGs could simply induce cell death through a non-specific effect.…”
Section: Discussionmentioning
confidence: 99%